Islamic Philanthropy and The Private Sector in Indonesia - Hilman Latief (IJIMS, 2013)
This paper investigates the growing initiatives within the private sector to organize social welfare activities, and analyzes the way in which zakat (alms) is practiced among Muslim businessmen. The establishment of zakat agencies within private companies has marked the latest trend of the practice of philanthropy in Indonesia. Corporation-based zakat collectors have become new players in the rapid growth of the Indonesia’s zakat sector in the past two decades. This paper examines the following issues: what are the main forces stimulating corporations to set up zakat collectors; what kinds of religious ideas are applied to mobilize charities from Muslim workers, and how these concepts are interpreted and practiced within private companies? This paper argues that the inception of a new concept in zakat practice, such as zakat on corporate wealth, has indicated the dynamics process of Islamization of the private sector in Indonesia.